Spread Trading : an Introduction to Trading Options in Nine Simple Steps. - Jensen, Greg (John Wiley & Sons, 2009)
A proven method for making the most of options. While professional investors are doing more and more in the way of options trading, nonprofessionals know little about this opportunity and the tremendous advantages it offers. This book provides readers with the basic tools to begin trading options through the best and safest method available: spread trading. With Spread Trading, Greg Jensen continues to educate individuals on the benefits of trading this way. And while most discussions about options trading do not emphasize how both parties in an options trade can come out ahead, Spread Trading.